Pengaruh Social Media Marketing terhadap Ekuitas Merek dengan Online Experiential sebagai Variabel Mediasi (Studi pada Konsumen Toko Busana Cordy Bandar Lampung) - Fitri Destiana Destiana (Universitas Bumigora, 2022)
This study aims to determine the effect of social media marketing on brand equity among consumers of Cordy Clothing Stores Bandar Lampung with online experiential mediation. This study used a descriptive quantitative method with data collection techniques through distributing questionnaires. The population in this study were consumers at the Cordy Fashion Store in Bandar Lampung. The author takes the type of probability sample, namely the simple random sampling method with a total sample of 100 people. Furthermore, to analyze the researcher uses a Likert scale with the method used is the partial least squares (PLS) approach. The results of the t-test test show that social media marketing and online experiential have a significant effect on brand equity. The R2 test shows that the magnitude of the online experiential R2 value is 0.634 and brand equity is 0.696. This value indicates that online experiential variables and brand equity, social media marketing support has an effect on experiential online by 0.634%, and brand equity by 0.696%. So based on the four steps taken to test mediation with the causal step, it can be concluded that experiential online mediates social media marketing relationships on brand equity which are positive and significant on brand equity by partial mediation or mediation occurs, where social media marketing variables can directly affect variables brand equity or indirectly and involves online experiential mediation variables or it can be said that online experiential mediates social media marketing relationships and brand equity.